2016
DOI: 10.1177/0969733016631161
|View full text |Cite
|
Sign up to set email alerts
|

Ethical dimensions of paediatric nursing: A rapid evidence assessment

Abstract: Few studies investigate the ethical dimensions and aspects of paediatric nursing, and they are mainly qualitative studies conducted in critical care settings based on nurses' perceptions and experiences. Paediatric nurses require specific educational interventions to help them resolve ethical issues, contribute to the decision-making process and fulfil their role as advocates of a vulnerable population (i.e. sick children and their families). Further research is needed to investigate how paediatric nurses can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 29 publications
1
16
0
6
Order By: Relevance
“…The proportion of ethical dilemmas among Slovenian HCPs is comparable with the findings of other studies that showed that between 60% and 90% of HCPs encountered various ethical dilemmas in their work [ 13 , 32 , 41 43 ]. Our findings concur with those of several international studies, which reported that not only physicians but also nurses and other HCPs may encounter different ethical dilemmas [ 42 , 44 46 , 47 ]. The demographic characteristics of our HCPs showed that the majority of our participants were female (79.5%).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The proportion of ethical dilemmas among Slovenian HCPs is comparable with the findings of other studies that showed that between 60% and 90% of HCPs encountered various ethical dilemmas in their work [ 13 , 32 , 41 43 ]. Our findings concur with those of several international studies, which reported that not only physicians but also nurses and other HCPs may encounter different ethical dilemmas [ 42 , 44 46 , 47 ]. The demographic characteristics of our HCPs showed that the majority of our participants were female (79.5%).…”
Section: Discussionsupporting
confidence: 92%
“…which reported that not only physicians but also nurses and other HCPs may encounter different ethical dilemmas [42,[44][45][46]47]. The demographic characteristics of our HCPs showed that the majority of our participants were female (79.5%).…”
Section: Plos Onementioning
confidence: 76%
“…As a result of the examination, 15 studies dealt with ethics and nursing together; 32,52,57 69 six studies addressed ethical difficulties/ethical dilemmas and nursing; 33,34,51,53,70,71 two studies were on ethical competence and nursing; 54,72 two studies were on nursing professional ethics; 14,73 one study was on ethics, education, and nursing; 74 and one study was conducted on ethics in health research. 75 It can be said that the search for equilibrium in the direction of findings obtained from studies with high level of evidence about nursing and ethics continued and that the common focal point of the researches concentrated on the preferences and characteristics of the nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in the field of ethics and nursing include the following subjects: care of patients who demand euthanasia and ethical interrogations of nurses, 59 ethical sensitivities of nurses, 65 moral courage of nurses, 52 ethical support mechanisms for older people care, 67 ethical dilemmas experienced by surrogate decision-makers, 61 ethical dimensions of pediatric nursing, 58 factors affecting professional values among nursing students and teachers, 66 ethical issues in nursing homes, 57 ethical situations faced by nurses in rare or unusual situations, 68 technology and ethics in nursing, 62 psychometric properties of the instruments measuring the quality of care and care ethics, 63 technical and ethical aspects of nursing care, 69 sexual and ethical situations in care homes, 64 publication ethics in the field of pediatric nursing, 32 and nurses’ decisions about physical restraint situations. 60 The versatility of the studies under this theme may be due to the fact that the nursing profession undertakes positions in many areas such as training, counseling, case management, and care.…”
Section: Discussionmentioning
confidence: 99%
“…"Being a good nurse" means: 1) being compassionate: feeling concern and sympathy for others; 2) being empathetic: the willingness to make a concerted effort to listen to patients, to see things from the patient's perspective and to attempt to understand patients' challenges; 3) being selfless: willing to make personal sacrifices for the sake of others; 4) being self-aware: possessing the emotional intelligence to understand oneself and one's values with reference to others, and to recognize one's personal strengths and limitations; 5) being caring, understanding, nonjudgmental, with the ability to empathize with patients and to control one's own emotions when dealing with stressful situations; 6) being able to communicate with physicians, patients and their relatives, and co-workers; and 7) being knowledgeable about how to perform all responsibilities with the utmost accuracy and thoroughness (Brammer, 2006;Bartz, 2010;McLean, 2011;Gokenbach, 2012). With regard to "being a good nurse", researchers mention nurses' competence (Meehan, 2012), the nurse-patient relationship (Benbow, 2013;Rørtveit et al, 2015), and the ethics of nursing (Lachman, 2012;Bagnasco et al, 2016). In the literature, "being a good nurse" is mostly described from the perspective of patients and nurses, with little from the that of nursing students.…”
Section: Introductionmentioning
confidence: 99%